Kegelisahan dan Perasaan Kolektif Digital Perempuan dalam Proses Merawat - Sofiatul Hardiah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
The development of communication technology allows muted people to express themselves in the social environment. Women serving as wives and mothers are a category of group still negotiating with patriarchal values that silence them. This article highlights the behavior of women as wives and mothers who share experiences and create a support ecosystem through the mediation of online conversation platforms. Through the perspective of feminism and affect theory with digital ethnographic data collection methods on The Asian Parent Indonesia platform, this paper aims to understand women's bodily experiences as part of representative knowledge production. This paper argues that digital conversation platforms create alternative spaces for nurturing and care that are limited in offline spaces, while mediating the process of feeling collectively among women who experience the bodily experience of being a wife or mother. The intersection of women, body, and digital technology shows that personal bodily experiences can establish collective bonds through the mobilization of emotions mediated by digital technology. Conversing with fellow women virtually is an effort to find a safe space for women who are silenced in the process of nurturing and caring in offline spaces.